Reuse process for timber elements to optimise residual performances in subsequent life cycles - Stefania De Gregorio (Vitruvio: International Journal of Architectural Technology and Sustainability)
The reuse of wooden elements is a sustainable operation, which makes the best use of the material’s grey energy. Currently, structural timber from selective demolition is mainly used for non-structural functions, with a lowering of its performance, due to the lack of standard and specific regulation. In fact, the visual grading used to define the structural characteristics of wood does not evaluate information deriving from the previous life cycles of the component. In the paper, taking samples of rectangular timber elements from selective demolitions made in the Valencian Community, the structural values that are assigned by visual strength grading legislation were compared with the real resistance values identified by experimental analysis to verify their compliance. The verification showed that the visual grading is not able to optimize the performance of the timber element in its reuse. Therefore, the purpose of the research, illustrated in the paper, is to find a reuse process for structural wooden elements to enhance residual performances. The identified process introduces additional steps compared in the current visual grading, that include a consideration of the effective modalities of reuse evaluated according to the worst defects and information arising from previous life cycles.